Women’s experiences of fistula-related stigma in Uganda: application of a conceptual framework to inform stigma-reduction interventions - Elayadi, Alison (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To understand women’s fistula-related stigma experiences using a conceptual framework. Methods: In-depth interviews and focus groups discussion including 33 women who underwent fistula surgery 6-24 months prior at Mulago Hospital in Kampala, Uganda in May-July 2014.Coded transcripts were analyzed thematically for experiences and consequences of enacted, anticipated, and internalized stigma. Results: Narratives of enacted stigma experiences included verbal abuse, relationship dissolution, and exclusion from household, family and community activities. Women’s stigma anticipations reflected fears of enacted stigma. Internalized stigma reports revealed pervasive shame and low self-esteem: reduction in self-worth, disgrace, and envisioning no future. Consequences of fistula-related stigma described by women included self-imposed social isolation, changes to normal household activities, non-disclosure of fistula, and poor mental health. Conclusions: Refining stigma theory to specific conditions has resulted in nuanced understanding of stigma dimensions, manifestations, mechanisms, and consequences, permitting comparison across contexts and populations, and development and evaluation of stigma-reduction interventions. These lessons should be applied to fistula, acknowledging its unique features: concealability, management needs, lack of community awareness, and links with infertility and stillbirth. Reducing fistula-related stigma requires timely access to surgical and supportive care, developing and evaluating evidence and theory-based interventions for social reintegration and stigma reduction, and addressing the complex societal structures perpetuating this condition.